The importance of proper public speaking for effective communication - TIVADAR, HOTIMIR (Anali PAZU HD, 2023)
Contemporary public communication is guided by the basic maxim of the modern world and life, i.e. by speed. Fast messaging often means short messaging, frequently superficial and with a lack of in-depth communication. In the foreground are short messages, which we send hastily, often thoughtlessly. That is why it is even more important that our message is correct and concise both in terms of language and content. Here, an important part is played by the Slovenian literary language, with its nationally representative and unifying role. In this paper, I want to show the importance of quality public communication (correctness, clarity, respect, and meaning of the message). The importance of content and rhetorically appropriate presentation of one’s views are often forgotten on a Slovenian and global scale. Performance can completely override content. In addition, I will present the unity of the Slovenian literary language, which is drawn through phonetic-phonological and orthographic analyses; even the pronunciation of literary vowels is clear and uniform regardless of the regional origin of the representative speakers in Slovenian public space.